ANALYSIS OF SLEEP QUALITY, RISK OF FALLS AND FUNCTIONAL CAPACITY IN PHYSICALLY ACTIVE ELDERLY: A CROSS-SECTIONAL STUDY (Movimenta (ISSN 1984-4298), 2023)
Introduction: Aging causes changes in the quality of sleep, which is considered a risk factor for falls, in addition to influencing the functional capacity of the elderly. Physical activity is considered a factor in preventing damage from aging. Objective: To assess sleep quality, risk of falls, and functional capacity in physically active elderly people. Methodology: a cross-sectional study, consisting of 29 elderly participants in the preventive physiotherapy program for the elderly in the basic health care internship of the physiotherapy course in the city of Uberlândia. The collection started with the questionnaires: the IPAQ (International Physical Activity Questionnaire), which evaluated the level of physical activity, and the MMSE (Mini-Mental State Examination), which measures cognitive impairment, both were used as inclusion criteria for the participants. From the inclusion, the instruments were applied: MSQ (Mini-Sleep Questionnaire) to assess sleep quality, and the Barthel Index which assessed functional capacity, and the TUG (Time Up and Go test) assessed the risk of falls. Results: The sample showed that 18 (62.06%) seniors had a good sleep, 21 (72.40%) seniors indicated a low risk of falls, and 22 (75.86%) seniors showed complete independence to perform activities of daily living. Conclusion: Most of the elderly evaluated in the study had good sleep, a low risk of falls, and total independence to carry out activities of daily living.
Keywords: Sleep; Aging; Daily Activities